The Application of Free Drawing Art Therapy on the Ability to Control Auditory Hallucinations in The Dewaruci Room of Dr. Amino Gondohutomo RSJD, Central Java - Devilya Pasimanyeku; Dwi Indah Iswanti (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Hallucinations are a mental disorder in which clients experience sensory perception disorders, resulting in false sensations of sound, taste, touch, sight, or smell. Clients with auditory hallucinations hear voices commanding and calling them to perform activities, consisting of two or more voices commenting on a person's behavior or thoughts. Auditory hallucinations are a stimulus disturbance in which clients hear voices, especially human voices. They typically hear voices discussing their thoughts and ordering them to do something. This study aims to describe the application of free-drawing art therapy in nursing care for patients with sensory perception disorders: auditory hallucinations in the DewaRuci Ward of Dr. Amino Gondohutomo Mental Hospital, Central Java. This case report involves three patients (Mrs. S, Mrs. R, and Mrs. A) who exhibited symptoms of auditory hallucinations. Nursing implementation was carried out over three sessions using a step-by-step approach, including techniques for reprimanding hallucinations, medication education, distraction through drawing and coloring, conversational practice, and encouragement to make drawing a routine. The evaluation results showed a significant decrease in indicators of verbalization, hearing whispers, and hallucinatory behavior. The patient experienced a decrease from the